Młodzi (nie)kompetentni w środowisku szkolnym - Agnieszka DOMAGAŁA-KRĘCIOCH; Bożena Majerek (Edukacja Ustawiczna Dorosłych)
The basics of human life skills are created from an early age. Initially, the responsibility for this process lies mainly with the parents, and over time also with the school. This article presents the procedure of constructing and standardizing the Life Competence Scale (LCS), which is an important element of life skills. As a result of statistical analyses, the subscale of positive competences and pseudo-competences was distinguished within LCS. The scale achieved a very high level of reliability and coherence.